ADAPTASI SOSIAL NELAYAN PENGERIH TRADISIONAL DI PESISIR KOTA DUMAI - rahmah husna yana; Triyanto Triyanto; Rachmatika Lestari (Universitas Teuku Umar, 2025)
Pengerih fishermen are traditional fishers living along the coastal area of Dumai City. However, their existence has significantly declined and is now nearly lost. This study aims to identify the factors contributing to the diminishing presence of pengerih fishermen in Dumai. The sociological analysis employs Talcott Parsons’ structural functional theory. A qualitative descriptive method was applied, with field data collected through interviews and direct observations with selected informants. Data analysis followed qualitative procedures involving data reduction, data presentation, and conclusion drawing. The findings reveal that the declining existence of traditional pengerih fishermen in coastal Dumai is driven by several factors: difficulties in producing pengerih fishing gear, challenges in adjusting fishing activities to tidal conditions, limited capital, and the loss of fishing grounds due to port development along the coastal area of Dumai City.